Inter- and intra-subject variability in gabapentin absorption and absolute bioavailability - Gidal, Barry E.; Radulovic, L.L.; Kruger, Sarah; Rutecki, Paul; Pitterle, Michael; Bockbrader, Howard N. (Epilepsy research, 2000)
Gabapentin (GBP) is a non-metabolized, non-plasma protein bound, renally excreted antiepileptic drug that is actively absorbed via the system L amino acid transporter. Previous studies have demonstrated that gabapentin displays dose-dependent absorption. Objectives: These studies were conducted to determine inter- and intra-subject variability of gabapentin absorption. Two prospective clinical studies in healthy adult volunteers were conducted. Coefficient of variation ( CV) was used to express variability of gabapentin absorption. Methods: Study A: 400-mg single dose, randomized, cross-over study to assess bioavailability of four different gabapentin formulations ( n=20, 9 males, 11 females; mean age and weight 41 years, 75.1 kg). Plasma was serially collected up to 48 h and bioavailability (F) calculated post-dose to determine concentration-time curves ( AUC). All four formulations were bioequivalent, thus repeated measures analysis was performed to assess inter-and intra-subject variability. Study B: 600-mg single dose study ( n=50, 15 males, 35 females; mean age and weight 31.1 years, 72.7 kg) was conducted to determine inter-subject variability in gabapentin F. Urine was collected over 48 h and bioavailability (F) calculated. Urine and plasma gabapentin concentrations were measured by HPLC-UV. Results: Study A: Overall mean ( CV) of GBP AUC values was 34.1±24 ug/h per ml. Inter-subject CV for AUC was 22.5% and intra-subject CV was 12.1%. Study B: Overall mean (SD) GBP F was 49.3±13.6%. Inter-subject CV of F was 27.6%. Discussion: The inter-subject variability in gabapentin absorption is substantially less than that of the inter-subject variability. This indicates that one would expect a wide range in gabapentin absorption between subjects; however, a much smaller variability within a subject. The within subject variability of gabapentin is small enough that plasma drug monitoring may be used to assess gabapentin absorption for a given subject and the benefit of dose individualization.